Analisis Finansial Usahatani Jeruk Siam di Kawasan Agropolitan Kecamatan Mandastana Kabupaten Barito Kuala - Dewi Hayati Ningsih; Yusuf Azis; Muzdalifah Muzdalifah (AGRIDES: Jurnal Agribisnis Perdesaan, 2013)
The study is expected to: (1) calculate the cost, revenue, and the profit of siam orange farming; (2) determine the farm feasibility by using revenue cost ratio (RCR) and profit rate; and (3) excavate the problem faced on the cultivation The study was conducted in Oesa Karang Bunga and Desa Karang Indah, Kecamatan Mandastana Kabupaten Barito Kuala The respondents were taken and distinguished based their land holding, i.e.: 25 farmers who owned 2 hectares of land, and 5 farmers who have less than 2 hectares. The study exposes that the average total cost IDR 12.77 mill ion per hectare, average revenue is IDR 49.96 million per hectare, and average profit is is IDR 36.19 milli on per hectare. The RCR value is 3. 84 which mean that siam orange cultivation is financially feasible since the RCR value is greater than 1.00. The profi t rate is 2.84%, much higher that fruit pric e inflation which accounted 0.0891% in Banjarmasin. Thus, the orange cultivation is financially feasible based on both RCR and profit rate criteria. However, several problems should be settled include the increase of pest and disease attack caused by unpredictable rainy season, difficulty in finding hired labors in busy season, and the lack of financial support.